Wakaf Uang : Solusi Meningkatkan Kesejahteraan Masyarakat di Masa Pandemi COVID-19 - Lubis, Rini Hayati; Lestari, Sri Indah; Harahap, Hawanisa (Journal of Islamic Social Finance Management, 2021)
The Covid-19 pandemic has resulted in a weakening of the people's economy, which has caused the economic growth of a country to decline, therefore an alternative is needed to increase economic growth, one of which is waqf. Currently, cash waqf has reached Rp. 244 billion with the total nazhir of cash waqf reporting 111 institutions while for cash waqf institutions reaching 272, meaning that around 161 institutions have not reported collected cash waqf funds due to a weak level of knowledge about the management of cash waqf. It can be concluded that the money waqf management system is still weak so that the cash waqf has not been realized to the public, but if the cash waqf funds are collected it will make a new instrument for the government to improve the economy, especially during this pandemic. The realization of good waqf funds will ultimately increase the level of trust in waqf management which is transparent and accountable, therefore it is hoped that there is a need for socialization to the public regarding the role of the money waqf, and providing training for Nazhirs to be able to manage these waqf based on technology.  Keywords: Cash Waqf, Covid-19 Pandemic, Welfare